Effects of Garlic and Green Tea as Alternative Feed Additives in Broiler Diet (Journal of the Bangladesh Agricultural University, 2024)
The objective of this study was to evaluate the use of garlic and green tea as alternative for safe broiler production. The experiment was done for a period of 35 days with 300 day-old Cobb-500 straight run broiler chicks. Birds were divided into five dietary treatment groups with four replications and each having 15 birds per replication. Treatments consisted as corn-soybean meal based basal diet and basal diet supplemented with 0% feed additives, 0.20% antibiotic, 0.25% garlic powder, 0.25% green tea powder and combination of garlic and green tea powder (0.125% garlic powder and 0.125% green tea powder). Body weight, feed intake of the bird were recorded every week, whereas dressing parameters, meat and bone development, serum biochemical parameters and hematological parameter were measured at the end of the experiment. Body weight, body weight gain increased (P